RANCANG BANGUN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATERI HARDWARE KOMPUTER DI SMK MUHAMMADIYAH 1 PADANG - Prastanti, Cinta Bening; Asmara, Delvi; Irfan, Dedy; Samala, Agariadne Dwinggo (Lembaga Pengembangan Kinerja Dosen, 2026)
Computer hardware learning in vocational high schools is often constrained by limited practicum equipment, restricting students' access to hardware components, while conventional media further limit independent study. This study aimed to develop an Augmented Reality (AR)-based learning medium for computer hardware material, integrating three-dimensional visualization, a gamified assessment, and an anti-tab-switching mechanism to support assessment integrity. The study employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate), with the Disseminate stage limited to a small-scale practicality trial. The AR application was developed using Unity 3D, Blender, and Vuforia SDK with marker-based tracking to visualize the motherboard, processor, RAM, hard disk, power supply, and VGA card. Product validity was assessed by three media experts and three material experts using Likert-scale instruments, while practicality was evaluated through a questionnaire administered to 10 students from a population of 20 Grade X Computer and Network Engineering students at SMK Muhammadiyah 1 Padang. The results showed media validity of 91.25%, material validity of 93.81%, and practicality of 94%, each categorized as very valid or very practical. These findings indicate that the developed AR-based media is feasible and practical for interactive, independent hardware learning while maintaining assessment integrity.